Teacher Education in Brazil and Uruguay: Guidelines for Integrating Digital Technologies into the Curricula - Rosso Guizzo, Michele Alda (2026)
This article examines the integration of topics related to digital technologies in the curricula of initial teacher education programs in Brazil and Uruguay in state and private universities. In both countries, the graduation profile envisions the didactic-pedagogical training of professionals to work in primary and secondary education. The choice of these two countries is based on their ongoing curricular reform processes and shared challenges, which offer a comparative perspective for critically identifying pathways to integrate technology into teacher training. The analysis focuses on the presence of courses dedicated to the pedagogical use of such technologies and the inclusion of content related to emerging technologies, such as Artificial Intelligence. The research was conducted in five stages: document selection, information mapping, topic categorization, results analysis, and finally, a proposal of guidelines for curricular development that addresses digital technologies in an integrated and innovative way. The research period spanned from February to June 2025. This is a qualitative, exploratory, and documentary-based study, grounded in the analysis of 65 Pedagogical Course Projects (PPCs) from teacher education programs in Brazil and teacher training syllabi from Uruguay. The findings reveal that, although there are relevant initiatives aimed at enhancing teachers’ technological education, these efforts are unevenly distributed across the institutions studied. Moreover, there is a noticeable lack of engagement with emerging topics and an absence of explicit alignment with public education policies. In light of these findings, the study proposes guidelines for curricular redesign that respond to contemporary demands for the integrated and up-to-date inclusion of digital technologies and emerging themes in teacher education.